Literature Review: Development of Science Learning Based on Local Wisdom and Indigenous Knowledge for ESD - Febrian, Andika; Wilujeng, Insih; Kun Prasetyo, Zuhdan (KnE Social Sciences, 2024)
The problem in science learning that often occurs today is that many students think that science learning is taught in an uninteresting and irrelevant manner. Science learning is irrelevant according to their perception because of the lack of connection and linkage of science learning with everyday life and the socio-cultural background they experience. One alternative solution to overcome the above problems and science learning becomes more relevant is necessary to revitalize the curriculum based on contextual concepts in accordance with the daily lives of students, like the cultural context of local wisdom or indigenous knowledge. This literature review was a scientific study of the analysis of 30 articles on science learning based on local wisdom and indigenous knowledge. This study aimed to analyze and elaborate on the integration of science learning with culture and its impact on education. This research was qualitative research using the descriptive analysis method of Miles and Huberman, which consisted of several steps: data collection, data reduction, data display, and conclusion. The articles analyzed were sourced from national articles indexed by SINTA and internationally reputable articles indexed by SCOPUS from 2017-2021. The results of this study indicated that science learning based on local wisdom and indigenous knowledge is considered very important as an innovation in ESD that affects the character and various abilities of students. These innovations can be carried out through revitalizing the science curriculum, developing learning products, and continuing scientific studies. Keywords: Science Learning, Local Wisdom, ESD